Eventful Man or Event Making Man? The Local Hero (1945-1950) Based on The Toponymy of Street Names in Palembang City - Aulia Novemy Dhita; Muhammad Reza Pahlevi; Khalidatun Nuzula; Rieca Nona Mutia; Salsabila Nofradatu; Tubagus Rizki Sunandar (Criksetra: Jurnal Pendidikan Sejarah, 2022)
Sidney Hook classifies the hero in history into two categories, namely eventful man and event making man. Using this approach, it can classify the fighter figures (1945-1950) in Palembang which are traced based on the toponymy of street names in Palembang City. The problem in this study is how to classify ‘the hero in history-Sidney Hook’ against the fighting figures (1945-1950) in Palembang based on the toponymy of street names in Palembang?. This study aims to describe the role and values of the struggle of the fighter figures (1945-1950) which are traced based on the toponymy of street names in Palembang City. This research uses historical methods in solving problems with heuristic stages, source criticism, interpretation and historiography. Based on the results of the study, it was obtained that most street names in Palembang use the names of fighter figures (1945-1950) in Palembang. Based on the classification of ‘the hero on history-Sidney Hook’, A.K. Gani (A.K. Gani Street) is an eventful man and an event making man. Abdul Rozak (Residen Abdul Rozak Street) and M. Isa (M. Isa Street) are making man events. In addition to these three fighter figures, there are many other fighter figures (1945-1950) in Palembang.